2014
DOI: 10.1038/ncomms6652
|View full text |Cite
|
Sign up to set email alerts
|

Mus81-Mms4 and Yen1 resolve a novel anaphase bridge formed by noncanonical Holliday junctions

Abstract: Downregulation of separase, condensin, Smc5/6, topoisomerase II and Cdc14 in Saccharomyces cerevisiae yields anaphase bridges formed by unresolved sister chromatids (SCBs). Here we report that the overlapping actions of the structure-selective endonucleases (SSEs) Mus81-Mms4/EME1 and Yen1/GEN1, but not Slx1-Slx4, are also essential to prevent the formation of spontaneous SCBs that depend on the homologous recombination pathway. We further show that the frequency of SCBs is boosted after mild replication stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 68 publications
2
66
0
Order By: Relevance
“…We propose that these simpler structures may be more important in vivo , perhaps because they are more frequently encountered. Consistent with this hypothesis, recent studies show that replicative stress in yeast results in nicked and gapped HJs, while another study highlights non-HJ intermediates of replication repair (56,57). …”
Section: Discussionmentioning
confidence: 64%
“…We propose that these simpler structures may be more important in vivo , perhaps because they are more frequently encountered. Consistent with this hypothesis, recent studies show that replicative stress in yeast results in nicked and gapped HJs, while another study highlights non-HJ intermediates of replication repair (56,57). …”
Section: Discussionmentioning
confidence: 64%
“…Our observation that LOH is much more common in chromosomes that have become trisomic argues for a direct linkage between mitotic recombination and defective chromosome segregation. In this regard, it has been recently shown that persistent recombination intermediates form anaphase bridges (García-Luis and Machín 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were treated and analyzed using a BD FACScalibur machine as previously described (Quevedo et al 2012;García-Luis and Machín 2014). Briefly, 300 ml of culture was taken and mixed with 900 ml of 100% ethanol.…”
Section: Fluorescence-activated Cell Sorting Analysismentioning
confidence: 99%
“…HR often leads to the formation of DNA joint molecules in which the two recombining DNAs are covalently connected by a four-way DNA junction or Holliday junction (HJ) [2527]. These intermediates can result in chromosome segregation defects if they are not processed before anaphase onset [2832]. …”
Section: The Origin Of Hr-ufbsmentioning
confidence: 99%
“…Persistent recombination intermediates that escape the attentions of BTR, or are refractory to dissolution (e.g. single HJs and D-loop structures), are processed by a second mechanism which involves structure-selective endonuclease (SSE)-mediated resolution [31,32,39,40]. There are two genetically distinct resolution pathways: one is mediated by the SLX1–SLX4, MUS81-EME1 and XPF-ERCC1 (SMX) tri-nuclease complex [27,31,4146], and the other is mediated by GEN1 endonuclease [4750].…”
Section: The Origin Of Hr-ufbsmentioning
confidence: 99%